Utilization of small broken riceberry flour in gluten-free bread - Rakkhumkaew, Numfon (Food science and technology international = Ciencia y tecnologia de los alimentos internacional, 2019)
The aim of this study was to develop gluten-free bread formulations based on small broken riceberry flour, by using different ratios of rice flour and xanthan gum. Small broken riceberry and rice flour could be classified as low in amylose content (15.70 g and 20.50 g/100 g dry matter for small broken riceberry and rice flour, respectively). Additionally, small broken riceberry flour contained a total phenolic and total anthocyanin content approximately 500 times higher than that of rice flour. The addition of increased amounts of small broken riceberry flour and xanthan gum resulted in darker coloured gluten-free bread. However, there was no significant difference regarding moisture and specific volume. The increase of small broken riceberry flour and xanthan gum also led to a significant increase in the firmness of bread crumbs. The sensory evaluation showed differences in flavour, texture and overall liking, since adding small broken riceberry flour tended to make gluten-free bread more favourable. Bread containing rice flour and small broken riceberry flour in the ratio of 30:70 and 1.0% xanthan gum was selected on the basis of the sensory quality. Moreover, such bread also contained high levels of total phenolic and anthocyanin content